Papers of Frank Evatt - Evatt, Frank; Whiteside, Janice (1908)
Two volumes of press cuttings (1908-1918 and 1912-1916), containing programs and reviews of theatrical shows held in Melbourne; and Harry Julius' Theatrical caricatures with marginal anecdotes by Claude McKay, Sydney, N.S.W. Bookstall Co. Ltd, 1912. This material was used by Janice Whiteside in preparation of her Master of Arts thesis (University of Melbourne) entitled: Theatre in Melbourne during the Great War.
Manuscript reference no. : MS 5815.
Guide to collections of manuscripts relating to Australia
Keywords: Evatt, Frank -- Archives; Theaters -- Victoria -- Archives